ASSESSMENT OF THE NURSES KNOWLEDGE REGARDING THE CARE OF MENINGITIS PATIENTS - TASLEEM , K; SADDIQUE , H; TASNEEM , SS (Biological and Clinical Sciences Research Journal, 2024)
Meningitis is a life-threatening condition requiring prompt and effective management. Nurses play a critical role in the care of meningitis patients, yet gaps in their knowledge can adversely impact patient outcomes. Objective: To assess the knowledge of nurses regarding the care of meningitis patients in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 142 nurses using a structured and validated questionnaire. Data were analyzed using SPSS version 26, with results presented as frequencies and percentages. Results: The study revealed that 41.5% of nurses demonstrated good knowledge about the definition of meningitis, but significant gaps were observed in understanding its types, prevention strategies, and medical management. While 41.5% correctly identified viruses as a major cause, only 31% recognized vaccination as a preventive measure. Nurses with higher qualifications and more clinical experience exhibited better knowledge compared to their counterparts. Conclusion: There are substantial gaps in nurses’ knowledge regarding meningitis care, particularly in prevention and management. Targeted training programs and updated clinical guidelines are essential to address these deficiencies and improve the quality of care for meningitis patients in Pakistan.